Graphs and Combinatorics - Nakamoto, Atsuhiro; Schiermeyer, Ingo.; Chen, Guantao; Ota, Katsuhiro; Koolen, Jack.; Hachimori, Masahiro; Ozeki, Kenta; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
Graphs and Combinatorics is an international journal devoted to research concerning all aspects of combinatorial mathematics. In addition to original research papers, the journal also features survey articles from authors invited by the editorial board. When preparing the manuscript, please read the instructions placed in the right column of this page.
Keywords: Combinatorics; Engineering design; Combinatorics; Engineering Design